PEMANFAATAN BIOMASSA GULMA PAITAN (Tithonia diversifolia) (Hemsley) A. Gray SEBAGAI PUPUK KOMPOS DALAM MENINGKATAN HASIL KACANG TANAH - Desy Aryani; Uswatun Nurjannah; Hasanudin Hasanudin (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2019)
[THE USE OF PAITAN BIOMASS (Tithonia diversifolia) (Hemsley) A. Gray AS A FERTILIZER IN INCREASING PEANUT YIELD]. Peanuts are one of the food crops having high economic value due to their nutritional content, especially high protein and fat. Peanut crop production has decreased due to infertile land with poor in nutrients. Efforts to increase peanut production is by including organic paitan (T. diversifolia) provision. This study aims to obtain the optimum dose of T. diversifolia compost on the yield of peanuts. This research was carried out in Pekik Nyaring Village, Bengkulu, with a height of ± 25 m above sea level, from February to April 2018. The design used was a complete randomized block design with a single factor consisting of 6 levels of treatment with four replications. Factor dosage of paitan compost fertilizer (T. diversifolia) is 0 tons/hectares, 5 tons/hectares, 10 tons/hectares, 15 tons/hectares, 20 tons/hectares, and 25 tons/hectares. Data were analyzed using analysis of variance at a 5% level. The results showed that the optimum dose of 15.5 tons/hectares produced 6.54 branches. The dosage of T. diversifolia compost 25 tons/hectares produced the highest number of pithed pods (36.08 pieces), the heaviest pith weighted pods (111.58 g), and the heaviest seed weight (87.06 g).